The Future and Foundation of the 'Journal for the Study of Religion, Nature and Culture' - Taylor, Bron (Journal for the study of religion, nature and culture, 2025)
A paramount responsibility of any scholar is to acknowledge the contributions of others to their own work. As I step back from my role as the long-term Editor in Chief of the Journal for the Study of Religion, Nature and Culture, who founded our journal and led the effort to create the scholarly society with which it is affiliated, it is time to do that, as well as to say something about what we have accomplished.